Special educational needs and disability the basics - Wearmouth, Janice (Routledge, 2023)
Special Educational Needs and Disability provides a clear, coherent overview of the historical development of the field of special educational, or additional learning or support needs and disability, and discusses important past and current social and political contexts in which this took place, as well as changes in the law across time. It offers broad coverage of a range of needs and disabilities, and how to effectively identify and support those young people who experience such needs. This revised fourth edition covers recent legislative changes across the UK, an expanded discussion of key areas such as social, emotional, and mental health, a new chapter on literacy difficulties, and further fair, balanced, and open discussion of up-to-date evidence that indicates how young people who experience barriers to their learning are affected by factors associated with such marketisation, for example competition between schools and the academies programme. Special Educational Needs and Disability serves as essential reading for trainee and practising teachers, members of governing boards in schools and colleges, policymakers, and all those working directly with learners and their families.